The Influence of Soil Conditioning on Soil Infiltration Rate in Urban Facilities - Searphin Nugroho; Wahyono Hadi (Department of Geography Education, University of Jember, 2021)
Several attempts have been made to increase the permeable area in the cities, which include the building of green facilities such as parks and urban forests. Since these areas were built with soil compaction, the potential for infiltrating water differs compared with the natural green area. Therefore, this research aims to analyze the influence of soil conditioning on the constant infiltration rate using variables such as soil compaction, texture, and the presence of vegetation cover in urban facilities. The data used were obtained through field infiltration measurement using a single ring infiltrometer. In this research, the analysis carried out includes soil texture, Horton equation, the difference between conditioned soils and control plots, and USDA hydrologic soil classifications. The results showed that all variables (soil compaction, the presence of vegetation cover, and soil texture) have a significant effect on the constant infiltration rate. Based on the soil conditioning, the infiltration rate is increased on the vegetated plots and decreased on the plots with the combination of vegetation and compaction, as well as the compacted plots. Furthermore, the effect of vegetation cover is more significant in silt loam textured soil, while the influence of compaction is more on clay textured soil. The potential constant infiltration rate on the plots of similar characteristics with green urban areas are on K2 and L2 with 2.698 mm/h and 1.525 mm/h, respectively. Therefore, these plots have a moderate runoff potential based on USDA hydrologic soil classification. Keywords: Compaction; Infiltration; Soil conditioning; Urban facilities Copyright (c) 2021 Geosfera Indonesia and Department of Geography Education, University of Jember This work is licensed under a Creative Commons Attribution-Share A like 4.0 International License